Defectos congénitos y exposición prenatal a material particulado en una población colombiana - Cuadrado-Grisales, Leidy Tatiana (2023)
Introduction: Air pollution is associated with adverse obstetric events. There isevidence of an association between exposure to high levels of particulate matter lessthan 10 microns (PM10) and birth defects. Objective: To determine the existence ofan association between birth defects and prenatal exposure of pregnant women toPM10 in a Colombian population. Methods: Retrospective case-control study. Casesof mothers of newborns with postnatally confirmed congenital defects and controlswithout congenital defects were included. Emission exposure was determined bytemporo-spatial disaggregation using ArcGIS® and georeferencing using gvSIG®,Google Earth® and Google Street View®, using previously published and validatedestimates for the city. Statistical analysis was performed using Jamovi-Stats Opennow®. Results: A total of 101 patients were included, corresponding to 31 cases and70 controls. There was an increased risk of developing birth defects after exposureto PM10 emissions above 2.23 Ton/year/250m2 (OR: 8.17; 95% CI: 1.61 – 41.46; p =0.011). Conclusions: There was a relationship between exposure to high levels ofPM10 and increased risk of birth defects in the population studied. Future researchon the relationship between environmental contamination and adverse obstetricevents is suggested.